2009
DOI: 10.1093/humrep/dep208
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms -1154G/A and -2578C/A in the vascular endothelial growth factor gene with decreased risk of endometriosis in Chinese women

Abstract: The VEGF-460/-1154/-2578 TGC, CAA, TAA and TAC haplotypes were associated with endometriosis. The -1154A and -2578A alleles may be protective against the development of endometriosis in North Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
4
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 34 publications
6
57
4
8
Order By: Relevance
“…A contribution of the VEGF -2578 A/C SNP to endometriosis was also observed in the Estonian population, as well as VEGF -460/-1154/-2578 TGC, CAA, TAA and TAC haplotypes to endometriosis in North Chinese females (50,51).…”
Section: Discussionmentioning
confidence: 65%
“…A contribution of the VEGF -2578 A/C SNP to endometriosis was also observed in the Estonian population, as well as VEGF -460/-1154/-2578 TGC, CAA, TAA and TAC haplotypes to endometriosis in North Chinese females (50,51).…”
Section: Discussionmentioning
confidence: 65%
“…The genotype C/C of the SNP rs699947 in the -2578 nucleotide position of the VEGF promoter, has been associated with higher levels of VEGF in blood mononuclear cells [12]. This polymorphism correlates with disease stages in which angiogenesis plays a critical role [9,[13][14][15]. Despite the high prevalence of aggressive prostate tumors in Mexico [16], there are no association reports between -2578 C/A VEGF polymorphism and risk of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the VEGF -2578C>A polymorphism may influence promoter activity and variations of VEGF protein levels among individuals. Although there is no report on the association between the -2578C>A polymorphism and MetS susceptibility, Liu et al (21) have reported that the -2578A allele is protective against the development of endometriosis in North Chinese women. In contrast, Maltese et al (22) reported that the AA homozygote of the -2578C>A polymorphism had increased susceptibility to colorectal cancer in the Italian population.…”
Section: Discussionmentioning
confidence: 99%
“…Although association between the haplotypes of the VEGF -2578C>A and -1154G>A polymorphisms and MetS patients has not yet been evaluated, several studies have reported that haplotypes of the VEGF polymorphisms may contribute to the susceptibility of individuals and the severity of a specific disease. For example, Liu et al (21) reported that the C-G-T, A-A-C, A-A-T and C-A-T haplotypes of the VEGF -2578C>A, -1154G>A and -460C>T polymorphisms are associated with endometriosis in North Chinese women. The A-A-G and A-G-G haplotypes of the -2578C>A, -1154G>A and -634G>C polymorphisms are associated with decreased VEGF gene transcription and lower plasma VEGF levels in patients with amyotrophic lateral sclerosis from Sweden, Belgium and England (32), less advanced melanoma in the English population (26), and the risk of acute cerebral infarction in the Chinese population (33).…”
Section: Discussionmentioning
confidence: 99%